Comparison of the Influence of the Chinese Lobby and the Israeli Lobby in the United States - D. B. Grafov (Vestnik MGIMO-Universiteta)
The article is about how pro-Israel and pro-China interest groups try to lobby on the ground of Capitol, White House and executive branch. The study of the lobbying results is based on «General theory of action» T. Parsons. It is concluded that for lobbying interests the main point will be the representation of the interests in the political and public spaces and the creating of advocacy and lobbying infrastructure. The ability of the Israeli lobby to achieve the goal can be explained, firstly, by political inclusion in the decision-making process, and, secondly, by almost axiomatic representation Israel interests through the national interests of the United States. The Israeli lobby can be considered as the religious lobby. It can use the possibilities of Jewish religious organizations in grass root action. Also this gives the opportunity to avoid the requirements of the LDA. From the point of view of the theory of Talcott Parsons, the success of the Israeli lobby is the cause of the action of a large number of actors that may form in large groups. Another advantage of the Israeli lobby is the ability of its members to get relevant information about the current situation in different spheres of political life in the U.S. The objective of the present study was to reveal the ways in which China lobby succeeds. The influence of China lobby on decision-making process in the United States can be explained through strong economic ties between American corporations and the Chinese market. When lobbying China uses numerous Chinese Diaspora in many States, as well as trying to interest of the former high-ranking American officials, granting them special privileges for doing business in China. In comparison to the Israeli lobby, the Chinese lobby has weaknesses. Chinese interest groups are not included in the political system of the USA and this is the disadvantage of the Chinese way of lobbying. Unlike Israel lobby Chinese one is external. The interests of the chinese pressure groups do not coincide with American national interests. Their actors are not rooted in the American political system.